Analisis Pengaruh Kualitas Pelayanan dan Kinerja Pegawai terhadap Kepuasan Masyarakat di Kelurahan Limusnungal Sukabumi - Dimas Fitrah Adi Putra; Ellin Herlina; Gian Fitralisma (MAMEN: Jurnal Manajemen, 2025)
This study aims to examine the influence of administrative service quality and employee performance on community satisfaction in the Limusnunggal sub-district, Sukabumi City. Public services, which fulfill citizens' fundamental needs and civil rights, are vital in human life, and the demand for improved public services has become a significant public expectation. The research employs a quantitative approach, focusing on employees in the Limusnunggal sub-district as the study's subject. A random sampling technique was used, with a sample size of 100 respondents. Data were collected through questionnaires and analyzed using multiple linear regression and hypothesis testing with SPSS version 23. The results indicate that both administrative service quality and employee performance have a positive and significant impact on community satisfaction, as evidenced by the t-test results of (4.482 > 1.987) for service quality and (5.374 > 1.987) for employee performance, with significance values of (0.000 < 0.05) for each variable. The F-test results (F_count = 232.023 > F_table = 3.090, sig = 0.000 < 0.05) further confirm a significant simultaneous effect. The coefficient of determination reveals that 82.4% of the variance in community satisfaction in Limusnunggal is explained by the quality of services and employee performance, while the remaining 17.6% is influenced by factors not addressed in this study.